Implementasi Metode Prototyping pada Perancangan Sistem Pengaduan Kekerasan Siswa SMK Al-Huda Bumiayu - Waluyo, Retno; Kusuma, Bagus Adhi; Khasanah, Fitrotul; Nugroho, Rizki (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Education is an important foundation in shaping the character and potential of the younger generation. Some issues that arise in the world of education include cases of violence, bullying, inappropriate behavior, or other problems that disrupt students' comfort at school. SMK Al- Huda Bumiayu, as an educational institution, has a moral and legal responsibility to protect students from all forms of violence, including bullying and inappropriate behavior. The handling so far, in case of violence, can be done by contacting the guidance counselor via WhatsApp or through the suggestion or complaint box for students. Through these two media, a problem arises regarding the data on incidents of violence occurring in the school, which is not well-documented because it is often not recorded in the logbook and the focus is on resolving existing problems. Additionally, the progress of handling these issues is also unknown, making it difficult for the principal to make policies related to handling violence in the school. The objective of this research is to develop a web-based student complaint system using the prototyping method to facilitate the reporting of violence by students in the environment of SMK Al-Huda Bumiayu. The results of this research conclude that the prototyping method can be used to create a violence reporting system for students at SMK Al-Huda Bumiayu and assist students in reporting violence they have experienced or witnessed.